2000
DOI: 10.1002/(sici)1099-1263(200001/02)20:1<69::aid-jat630>3.0.co;2-2
|View full text |Cite
|
Sign up to set email alerts
|

Results of the l5178y mouse lymphoma assay and the balb/3t3 cellin vitro transformation assay for eight phthalate esters

Abstract: Eight phthalate esters, with alcohol chain lengths of 1–11 carbon atoms and with various degrees of branching, were tested in vitro in the L5178Y mouse lymphoma mammalian cell mutation assay and in the Balb/3T3 cell transformation assay. The tests were performed as part of a voluntary testing agreement between the Chemical Manufacturers Association’s Phthalate Esters Panel and the United States Environmental Protection Agency (US EPA). The esters tested were: dimethyl phthalate (DMP), di‐n‐butyl phthalate (DBP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
14
0
3

Year Published

2000
2000
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(18 citation statements)
references
References 25 publications
1
14
0
3
Order By: Relevance
“…DINP was not mutagenic in Salmonella (McKee et al, 2000;Zeiger et al, 1985) or mouse lymphoma cells (Barber et al, 2000), did not induce unscheduled DNA synthesis in primary rat hepatocytes (Litton Bionetics, 1981), and generally failed to induce phenotypic transformation of BALB/C-3T3 mouse cells either with or without metabolic activation (Barber et al, 2000). In addition, DINP tested negative in various in vitro and in vivo Microbiological Associates, 1981) chromosome damage assays.…”
Section: Genotoxicitymentioning
confidence: 99%
“…DINP was not mutagenic in Salmonella (McKee et al, 2000;Zeiger et al, 1985) or mouse lymphoma cells (Barber et al, 2000), did not induce unscheduled DNA synthesis in primary rat hepatocytes (Litton Bionetics, 1981), and generally failed to induce phenotypic transformation of BALB/C-3T3 mouse cells either with or without metabolic activation (Barber et al, 2000). In addition, DINP tested negative in various in vitro and in vivo Microbiological Associates, 1981) chromosome damage assays.…”
Section: Genotoxicitymentioning
confidence: 99%
“…Environmental Protection Agency (U.S. EPA) 1993b]. No evidence of other effects in animals at lower NOAELs exists (Api 2001; Barber et al 2000; Gray et al 2000). …”
mentioning
confidence: 99%
“…Cancer induction in rats appears to exhibit a threshold for hepatocellular carcinoma (Butala et al, 1996;David et al, 1999). Phthalates have tested negative in most short-term mutagenicity bioassays and thus appear to function through nongenotoxic/epigenetic mechanisms (Barber et al, 2000;Huber et al, 1996;Zeiger et al, 1985;McKee et al, 2000). While the mechanism of liver tumor induction is not clearly understood, our group has recently shown that induction of peroxisomal proliferation in rodent liver by several phthalates along with inhibition of gap junctional intercellular communication correlates with carcinogenic potential .…”
mentioning
confidence: 99%